Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1098611120907870
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Perceptions of Barriers to a Police Patrol Career

Abstract: Policing as an institution has been under immense pressure to increase the representation of women as police patrol officers. As the representation of women in policing has plateaued, increasing research has focused on barriers to women entering patrol work but has not examined the salience of these barriers with respect to males or reliably determined which barriers are most influential to desire to enter a police patrol career prior to employment. Drawing upon survey responses from more than 640 students enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
(89 reference statements)
0
21
1
Order By: Relevance
“…An emerging area regarding recruitment is concerns about career entry (Cambareri & kuhns, 2018;Lord & Friday, 2003;Rossler et al, 2020;Todak, 2017). Literature on motivation emphasizes that behavior is inspired by two sides of the motivational coin: (a) hopes and expectations and (b) fears or concerns 1 (Markus & Nurius, 1986).…”
Section: Potential Concerns and Gendermentioning
confidence: 99%
See 3 more Smart Citations
“…An emerging area regarding recruitment is concerns about career entry (Cambareri & kuhns, 2018;Lord & Friday, 2003;Rossler et al, 2020;Todak, 2017). Literature on motivation emphasizes that behavior is inspired by two sides of the motivational coin: (a) hopes and expectations and (b) fears or concerns 1 (Markus & Nurius, 1986).…”
Section: Potential Concerns and Gendermentioning
confidence: 99%
“…Even if women are attracted to policing, experiences with, or concerns about, discrimination could discourage them from pursuing it. A few studies have found that young women have concerns about gender as a barrier to a career in policing (Cambareri & kuhns, 2018;Lord & Friday, 2003;Rossler et al, 2020;Todak, 2017), and these concerns are not unfounded. There is plenty of evidence that issues of gender equity and fair treatment still exist in law enforcement.…”
Section: Potential Concerns and Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…While this study serves as an important first step in assessing perceptions on drug disqualifiers by both potential police applicants and those hiring them, there is still a great deal of work that can be done moving forward. Future research should use multivariate models to examine different demographic factors that may influence the perspectives on drugs and other police career issues (see Rossler et al, 2019, 2020), as well as find ways to survey samples more representative of police applicants. Furthermore, it would also be valuable to examine the perspectives of both chiefs and students in other states to better understand the generalizability of these findings and the potential for similar or different rule change recommendations.…”
Section: Discussionmentioning
confidence: 99%